The Psychologisation of Eastern Spiritual Traditions: Colonisation, Translation and Commodification - Cohen, Elliot (Concepts for Critical Psychology Ser., 2021)
Intro -- Half Title -- Series Page -- Title Page -- Copyright Page -- Contents -- Acknowledgements -- Preface -- 1. 'East is East and West is West?' -- The Atavistic East, the Mystic East and the Scientific East -- From the noble savage to the Mystic East -- The conquering Mystic East -- The World Parliament of Religions - the 'Scientific East' and the dawning of psychologisation -- The idealised 'East' -- The beginnings of buddhist psychology -- 2. Counterculture and the return to the East -- The way of Watts -- Encountering the 'counterculture' -- The 'counterfeit infinity' of the Kali Yuga -- 3. The Buddha as a psychologist, the Dharma as a psychotherapy -- The Buddhist wheel of life -- Beyond psychology -- Buddhism on the couch -- Buddhism as cognitive psychology -- Buddhism and neuroscience - within the machine -- 4. The Dao of psychologisation -- Jung and Daoism -- Humanistic Daoism -- Maslow's 'Taoistic' science and psychology -- Daoism, Ecopsychology and the Ecological Unconscious -- Idealising and denaturing Daoism - The Dao of cognition -- 5. The commodification of 'the East' -- The mystery of the Crouching Buddha -- The East in popular culture -- The Holy Man effect - orientalist ventriloquism -- Marketing and mechanising mindfulness -- Meditation and machines -- 6. Resistance -- Clapping for our NHS -- Idealising Eastern resistance -- Between woke and awakened -- Between woke and awakened - a middle way -- 7. Transpersonal psychology -- Psychology and religion - the return of the repressed -- The many meanings of critical -- Wisdom and warnings from Ladakh -- Transpersonal and Critical Psychology -- Transpersonal psychology as Critical Psychology -- References -- Index.